Kedudukan Audit Medis dalam Penegakan Hukum Tindak Pidana di Bidang Medis - Hamdani Abubakar (Lex Renaissance, 2018)
This study examines the status of Medical Audit in law enforcement in the medical field, and to what extend can Medical Audit be used as evidence in court proceedings. The concept of this research is juridical-empirical, with descriptive-qualitative study, the method used is literature and interviews, relying on legislation relating to health services in hospitals. This study uses a theory consisting of health legal instruments relating to ethics and law, Hospital Law, Medical Records, Medical Audits, Professional Standards, and Operational Procedure Standards, as well as materials for criminal actions and criminal accountability. The results showed that Medical Audit can be applied in investigations and inquisitions by the police. However, the police do not use Medical Audit as an instrument of enforcement and verification, whilst it is very crucial in assessing a certain relevant issue. Law enforcement is expected to be able to make the Medical Audit as part of the admissible evidence in the Police.